2018
DOI: 10.1161/jaha.118.009938
|View full text |Cite
|
Sign up to set email alerts
|

Renal Denervation Reduced Ventricular Arrhythmia After Myocardial Infarction by Inhibiting Sympathetic Activity and Remodeling

Abstract: Background Ventricular arrhythmia after myocardial infarction is the most important risk factor for sudden cardiac death, which poses a serious threat to human health. As the correlation between autonomic nervous systemic dysfunction and heart rhythm abnormality has been gradually revealed, remedies targeting autonomic nervous system dysfunction, especially the sympathetic nerve, have emerged. Among them, renal denervation is noted for its powerful effect on the inhibition of sympathetic nerve act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 47 publications
3
33
0
1
Order By: Relevance
“…RSD decreases spontaneous VAs in porcine models of ischemia rates of spontaneous VAs in porcine models of ischemia . In a canine study of myocardial ischemia, RSD led to decreased whole‐body and local tissue sympathetic activity and reversed neural remodeling in the heart and stellate ganglion . This resulted in beneficial electrophysiological changes in border zones of infarcts, culminating in decreased VAs .…”
Section: Effects Of Neuromodulation On Ventricular Arrhythmiasmentioning
confidence: 97%
See 2 more Smart Citations
“…RSD decreases spontaneous VAs in porcine models of ischemia rates of spontaneous VAs in porcine models of ischemia . In a canine study of myocardial ischemia, RSD led to decreased whole‐body and local tissue sympathetic activity and reversed neural remodeling in the heart and stellate ganglion . This resulted in beneficial electrophysiological changes in border zones of infarcts, culminating in decreased VAs .…”
Section: Effects Of Neuromodulation On Ventricular Arrhythmiasmentioning
confidence: 97%
“…[94][95][96] In a canine study of myocardial ischemia, RSD led to decreased whole-body and local tissue sympathetic activity and reversed neural remodeling in the heart and stellate ganglion. 97 This resulted in beneficial electrophysiological changes in border zones of infarcts, culminating in decreased VAs. 97 There have also been a few small studies in patients with refractory VAs or VT storm that showed a reduction in VAs after RSD.…”
Section: Blockade Of Sympathetic Neurotransmissionmentioning
confidence: 99%
See 1 more Smart Citation
“…55 In addition, the utility of RND in both atrial and ventricular arrhythmias. [56][57][58][59] The utility of RDN in HF patients was first reported in the Rehabilitation Enhancing Aging Through Connected Health (REACH) Pilot study. 60 Patients with chronic symptomatic HF on optimal medical therapy underwent RDN.…”
Section: Renal Nerve Denervationmentioning
confidence: 99%
“… 15 The beneficial effect of RDN has been demonstrated in HF. 16 , 17 However, the underlying mechanism is unclear.…”
Section: Introductionmentioning
confidence: 99%